GAMBARAN FAKTOR KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA - Ompusunggu, Fransiska; Pabontong, Angelika Septiani; Juliana, Anggi; Pakpahan, Friska Septiani; Silalahi, Elfrida (JURNAL KEPERAWATAN, 2025)
Abstract Background: Acute Respiratory Infections (ARI) are the leading cause of infectious disease morbidity and mortality in the world. Almost 156 million cases of ARI occur in toddlers in the world and increase every year with the highest percentage being in developing countries including Indonesia. Objective: This study aims to determine the description of ARI incidence factors in toddlers. Methods: The design used in this study was descriptive quantitative with purposive sampling technique, the research sample 89 respondents. The instruments used in this study were questionnaires and KMS. Data analysis using univariate analysis. Results: Based on the results, it shows that the individual factors of the mother's aged 30-59 years 52 (58.4%), the mother's education is high school-College 53 (59.6%), the mother's knowledge is in the good category 73 (82%). While the individual factors of toddlers in the age range of 1-3 years as many as 55 toddlers (61.8%), the gender of toddlers is predominantly male as many as 52 toddlers (58.4%), complete immunization status as many as 65 toddlers (73.0%), normal birth weight 79 toddlers (88.8%), get exclusive breastfeeding 77 toddlers (86.5%). Conclusion: The results showed that the incidence factor of ARI was the individual factor of toddlers (age 1-3 years and male gender). Keywords: Toddlers; Incidence Factors; Acute Respiratory Infection